Injury incidence according to athlete impairment type during the 2012 and 2016 Summer Paralympic Games: a combined analysis of 101 108 athlete days - Adam, F.; Derman, W.; Schwellnus, M.; Boer, P.-H.; Jordaan, E.; Runciman, P. (British Journal of Sports Medicine, 2024)
Objectives The relationship between sport-related injuries and Para athlete impairment type has not yet been comprehensively studied. This study aimed to describe injury incidence according to athlete impairment type during the London 2012 and Rio 2016 Summer Paralympic Games, by sex, age, Games period, chronicity and anatomical area.